FILSAFAT DIALEKTIKA HEGEL: RELEVANSINYA DENGAN PEMBUKAAN UNDANG-UNDANG DASAR 1945 - . Suyahmo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
The type of Hegel’s philosophical system is ‘dialectic‘, i.e it synthesizes subjective idealism type of Fichte’s philosophy and objective idealism type of Schelling’s philosophy. For Hegel, Fichte’s philosophy is named as ‘thesis’ and Schelling’s philosophy is named as ‘antithesis’. Whereas Hegel’s philosophy itself is named as synthesis of both, so the dialectic of Hegel’s philosophy consists of three phases, namely, thesis-antithesis-synthesis. Synthesis as the mediator of thesis and antithesis internally still contains the truth value from thesis and antithesis. The famous proposition which then makes Hegel become more popular is: “all real things are rational and all rational things are real.”This proposition and his dialectical concept: thesis-antithesis-synthesis, is relevant to examine the Preamble of the 1945 Constitution (Pembukaan Undang-Undang Dasar 1945). The main point is thesis (colonization) against antithesis (struggle) and then the result is synthesis (independence).